Dialektika Akidah dan Moralitas dalam Hadis(Analisis Teologis-Etik terhadap Karakter Muslim Ideal) - Muhammad Fauzen; Babun Najib (Al-Hasyimi: Jurnal Ilmu Hadis, 2025)
The phenomenon of dichotomy between faith and morality in the religious practices of contemporary Muslims shows a reduction in the comprehensive meaning of Islam. Many individuals claim faith theologically but fail to realize it in ethical social behavior, thus causing a crisis of spiritual and moral integrity. Departing from these problems, this study aims to analyze in depth the dialectical relationship between faith and morality in the hadiths of the Prophet Muhammad, and to formulate an ideal Muslim character model that is integral from a theological and ethical perspective. This research was conducted through a qualitative approach based on library research. The main sources were obtained from classical and contemporary literature, especially authoritative hadith books such as Sahih al-Bukhari, Sahih Muslim, Sunan al-Tirmidzi, and al-Adab al-Mufrad, as well as the works of Islamic scholars and thinkers who discuss the theological and ethical dimensions in Islam. The analytical method used is content analysis and text hermeneutics, with a focus on identifying themes of faith and morals, as well as conceptual and applicative relationships between the two in shaping Muslim character. The results of the discussion show that the hadiths form a construction of Muslim personality that emphasizes the balance between inner belief and outward moral expression. Aqidah is not only positioned as a theoretical belief, but as a spiritual force that drives concrete ethical actions. Hadiths such as